Surface immobilization of bone morphogenetic protein 2 via a self-assembled monolayer formation induces cell differentiation - Pohl, Theresa Lucie Maria; Knaus, Petra; Cavalcanti-Adam, Elisabetta A. (Acta biomaterialia, 2012)
Bone extracellular matrix consists of a network of proteins in which growth factors, like bone morphogenetic protein 2 (BMP-2), are embedded and released upon matrix turnover and degradation. Recombinant human (rh)BMP-2 shows promise in enhancing bone fracture repair, although issues regarding finding a suitable delivery system still limit its extensive clinical use. The aim of this study is to determine which cell activities are triggered by the presentation of immobilized rhBMP-2. For this purpose gold surfaces were first decorated with a self-assembled monolayer consisting of a hetero-bifunctional linker. rhBMP-2 was covalently bound to the surfaces via this linker and used to investigate the cellular responses of C2C12 myoblasts. We show that covalently immobilized rhBMP-2 (iBMP-2) initiates short-term signaling events. Using a BMP-responsive reporter gene assay and western blotting to monitor phosphorylation of Smad1/5/8 we prove that iBMP-2 activates BMP-dependent signal transduction. Furthermore, we demonstrate that iBMP-2 suppresses myotube formation and promotes the osteoblast phenotype in C2C12 cells. The bioactivity of surface-bound rhBMP-2 presented in this study is not due to its release into the medium. As such, our simple approach paves the way for the controlled local presentation of immobilized growth factors, limiting degradation while still maintaining biological activity.
Available online 20 October 2011
Gesehen am 06.06.2018